Patient Knowledge and Attitudes towards Genetic Testing in Parkinson’s Disease Subjects with Deep Brain Stimulation - Avram Fraint; Bichun Ouyang; Leonard Verhagen Metman; Carolyn Jones; Deborah A. Hall; Karen Marder; Gian Pal (Parkinson's Disease)
Objectives. As genetic testing is becoming more widely commercially available for Parkinson’s disease (PD) and may have implications regarding clinical outcomes for deep brain stimulation (DBS) and other therapies, we aimed to determine patient knowledge and attitudes towards genetic testing. Methods. A sample of 88 PD subjects with bilateral STN-DBS completed a Genetic Attitudes Questionnaire (GAQ). Knowledge and attitudes towards genetic testing were assessed. Results. The mean percent of correct responses regarding genetic testing knowledge was 58.5%. Nearly 90% of subjects were unfamiliar with Genetic Information Nondiscrimination Act (GINA). The most important reasons subjects cited in deciding whether to undergo genetic testing included (1) to be a candidate for clinical trials if positive, (2) to learn that they do not carry a mutation, and (3) because a healthcare provider had recommended it. Individuals who influence decision-making include spouses and children. About 88% of subjects would share results with spouses, children, and siblings. Discussion. These results reveal that there is a major knowledge gap regarding genetic testing in PD and the implications of testing results on treatment, work, insurance, and privacy. Also, subjects would mainly seek genetic testing to participate in clinical trials, with spouses and children being the key stakeholders in decision-making.